PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT. INNO WANGSA OILS AND FATS - Hartono, Eric; Vincent Tristan, Radick; Liangga, David; Daniel, Daniel; Michael, Michael (EDUTECH CONSULTANT, 2019)
This study aims to examine and analyze the effect of compensation and physical work environment on employee performance at PT Inno Wangsa Oils And Fats. Data collection was used in this study in the form of questionnaires, interviews and documentation. The data sources used in this study are primary data and secondary data. The data analysis technique used by the author in the form of multiple linear regression analysis serves to determine the effect / relationship of the independent variable with the dependent variable, validity test and reliability test, Classical Assumption Test and Hypothesis Test / Goodnes of fit test. Based on the results of the research partially, it shows that only compensation variables have a positive and significant effect on the performance of employees at PT. Inno Wangsa Oils And Fats. While the results of testing simultaneously show that compensation behavior and physical work environment have a positive and significant effect on employee performance at PT. Inno Wangsa Oils And Fats.